Educational methodological tools for the prevention of parasitosis in school-age children in the districts of Lima, 2023 - Rojas Aire , Joel Ivan (2024)
Objectives: Determine if training to prevent parasitosis in Peruvian school children was effective. Human beings face various diseases caused by different pathogenic agents, one of them is parasitosis, which often go unnoticed in Latin American countries. The prevalence of parasitosis is high, affecting individuals, families and communities. The lack of sanitation and cultural practices contribute to its spread, with the most vulnerable populations being those in poverty, immunosuppressed people, older adults and children. In Peru, the lack of education has increased the prevalence of these infections, which highlights the need to develop educational interventions, through awareness workshops, for their prevention, especially in school populations to raise awareness about the risks of the disease and the importance of hygiene and prevention of parasitosis. Material and Methods: 10 primary education educational institutions in the province of Lima were selected and different types of learning methodologies were developed in a didactic manner such as puppet shows, theaters, sketches, recreational games in addition to the use of triptychs and banners where the activities are described. most common forms of parasitic transmission in the population. Various questions were applied through a questionnaire to verify that the information has been assimilated. The data were evaluated with SPSS statistical software version 25. Results: The data indicated that the answers obtained in the questionnaire are reliable and validate the correct learning by the children. Conclusions: It can be concluded that our trainings were effective in preventing parasitosis in children at the selected institutions, although continued efforts and future research are required to address challenges and improve sustainability. We highlight the importance of educational approaches and community collaboration for success and sustainable development.